Impact Analysis of Community Service Activities: Conservation of Kendedes Water Sources in Candirenggo Village Singosari District, Malang Regency: Analisis Dampak Kegiatan Pengabdian Masyarakat: Konservasi Sumber Air Kendedes Di Kelurahan Candirenggo Kecamatan Singosari Kabupaten Malang - Gatot Soebiyakto; Nurida Finahari; Gatut Rubiono (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Many people's water needs are still met by using groundwater sources. Various efforts to conserve water sources need to be made to maintain the continuity of water supply for the community. Water source conservation is a conservation effort that can provide positive impacts from various aspects. The aim of preparing this article is to analyze the impact of Kendedes water source conservation community service activities in Candirenggo Village, Singosari District, Malang Regency. Community service activities have been carried out based on grants from the Director General of Higher Education's Community Partnership Program and internal university funds. The activities carried out include repairing cement floors, changing rooms, river crossings, stairs to the river, adding rubbish bins and outreach activities. The analysis was carried out based on data and information collection through direct observation and interviews with stall owners, inner tube float rentals, vegetable farmers, parking attendants and the user community. The analysis results show positive impacts from economic, environmental and social aspects.